2019
DOI: 10.1016/j.bej.2019.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Protein engineering of cellobiose dehydrogenase from Phanerochaete chrysosporium in yeast Saccharomyces cerevisiae InvSc1 for increased activity and stability

Abstract: Phanerochaete chrysosporium cellobiose dehydrogenase was cloned and expressed in S.cerevisiae.Enzymatic assay in microtiter plates based on 2,6-dichloroindophenol was optimized.Several mutants of cellobiose dehydrogenase with increased activity were found.Recombinant cellobiose dehydrogenases were purified and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…In general, our experiments confirmed that the replacement of methionine residues can improve stability against oxidative damage as shown previously, 42 , 58 but it also appears to be coupled to a loss in structural stability not immediately evident at short time scale, especially when these substitutions are within the hydrophobic core of the protein. It has been shown previously that mutations, especially in the core of a protein, frequently result in a decrease of the thermodynamic stability.…”
Section: Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, our experiments confirmed that the replacement of methionine residues can improve stability against oxidative damage as shown previously, 42 , 58 but it also appears to be coupled to a loss in structural stability not immediately evident at short time scale, especially when these substitutions are within the hydrophobic core of the protein. It has been shown previously that mutations, especially in the core of a protein, frequently result in a decrease of the thermodynamic stability.…”
Section: Results and Discussionsupporting
confidence: 90%
“… 40 Two recent studies described the negative effects of H 2 O 2 on the stability of CDH, and the authors showed that the replacement of methionine residues can improve the chemical stability of CDH. 41 , 42 However, both studies focused on the effects of externally supplied H 2 O 2 , and only limited data are available on the effects of turnover-related ROS production. In general, engineering turnover stability of enzymes is much less explored compared to directed evolution efforts toward higher activities, increased solvent/temperature stabilities, or novel activities.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the native secretory leader sequence gave three times higher expression than a signal sequence of α-factor [39]. Also, in research conducted earlier in our laboratory, the ability of S. cerevisiae to produce cellobiose dehydrogenase was confirmed, but the yields of the expressed enzymes were not high [40]. The results of work [39,40], both using the native secretion signal of CDH, are very different due to the use of different yeast strains.…”
Section: Cdhmentioning
confidence: 87%
“…Also, in research conducted earlier in our laboratory, the ability of S. cerevisiae to produce cellobiose dehydrogenase was confirmed, but the yields of the expressed enzymes were not high [40]. The results of work [39,40], both using the native secretion signal of CDH, are very different due to the use of different yeast strains. In work [39], the protease-free S. cerevisiae BJ5465 strain was used that can give high amounts of protein after long fermentation times.…”
Section: Cdhmentioning
confidence: 89%
“…The disadvantages of wild-type chitinases can be overcome by combining heterologous expression with the redesign of chitinases using molecular evolution, which involves consecutive rounds of mutation and selection to isolate clones with improved properties. Directed evolution has been applied to a variety of enzymes with industrial applications, such as glucose oxidase [ 9 , 10 ], P450 monooxygenases [ 11 ], cellulases [ 12 ], peroxidases [ 13 ], cellobiose dehydrogenase [ 14 ], transaminases [ 15 ], esterases [ 16 ], lipases [ 17 ], proteases [ 18 ], and many more. However, there are only a few examples of the directed evolution of chitinases [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%